Influence of a rider's rapid weight-shifting motion on the braking behavior of a self-balancing personal mobility vehicle. (2nd April 2016) - Jeong, Seonghee; Kouzai, Kazuki; Noguchi, Shinji
Abstract : Self-balancing personal mobility vehicles (PMVs) that use an inverted pendulum technique have attracted significant attention, but such vehicles have unique safety issues not found in conventional PMVs arising from their inherently unstable mechanisms. The objective of this study is to clarify the distinctive features in the rapid-braking motion of a rider and to investigate the influence of these features on a PMV's braking performance. In this study, we analyzed a self-balancing PMV without an operating handle. First, we measured the center of pressure (CoP) while a subject moved his body backward rapidly on an unstable boarding plate. From the experiment, we could observe a reverse reaction of the subject in which the CoP moved forward although the subject tried to shift his body backward. To investigate the influence of reverse reaction on braking performance, several rapid-braking simulations and experiments were conducted. From the results, it was revealed that the reverse reaction worsened the braking performance of the PMV. This conclusion will be valuable information for developing an emergency braking strategy to improve the braking performance of a self-balancing PMV. One possible emergency braking assist control is also proposed, which uses the differential value of the reaction force in the reverse reaction behavior. Through emergency braking simulations, it was confirmed that the PMV could be quickly decelerated by the proposed braking assist control. Graphical Abstract: